Neglected Posterior Subtalar Dislocation: A Case Report and Operative Technique - Aditya Priherdadi; Raden Andri Primadhi (Majalah Kedokteran Bandung, 2021)
Posterior subtalar dislocation is an exceedingly rare entity. Early anatomic reduction, initially by closed means, is crucial. Failure to recognize this condition or any occurrence of neglect will complicate the management and worsen the outcome. There are a handful of case reports on posterior subtalar dislocation and even less for neglected cases. This study reports a neglected subtalar dislocation in a 26-year-old male who worked as a driver and had experienced high-energy trauma due to car collision. This patient was managed by open reduction and pinning, and was followed up 2 months later with a good outcome. This technique was selected to be able to achieve functional motions without pain.